2012
DOI: 10.1039/c2ob26079d
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric organocatalytic diboration of alkenes

Abstract: The use of chiral alcohols to form the Lewis acid-base *RO(-)→ bis(pinacolato)diboron adduct, in situ, provides an opportunity to induce asymmetry in the organocatalytic diboration of alkenes and complements the well established transition metal-mediated enantioselective diboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…[165] In the system reported by Fernandez, methoxide anion (generated from the crucial base and methanol additives) is proposed to activate the diboron reagent, generating an sp 2sp 3 diboron species.Inalater publication, Fernandez was able to achieve moderate levels of enantioselectivity (up to 42 % ee)for the diboration of unactivated terminal olefins,through the use of chiral alcohol additives. [166] Thec hiral alkoxides presumably interact with the diboron reagent, allowing for moderate level of asymmetric induction. Morken and coworkers later considerably improved the asymmetric metalfree diboration of alkenes through the use of chiral diols.…”
Section: Transition-metal-catalysed Borylative Difunctionalization Rementioning
confidence: 99%
“…[165] In the system reported by Fernandez, methoxide anion (generated from the crucial base and methanol additives) is proposed to activate the diboron reagent, generating an sp 2sp 3 diboron species.Inalater publication, Fernandez was able to achieve moderate levels of enantioselectivity (up to 42 % ee)for the diboration of unactivated terminal olefins,through the use of chiral alcohol additives. [166] Thec hiral alkoxides presumably interact with the diboron reagent, allowing for moderate level of asymmetric induction. Morken and coworkers later considerably improved the asymmetric metalfree diboration of alkenes through the use of chiral diols.…”
Section: Transition-metal-catalysed Borylative Difunctionalization Rementioning
confidence: 99%
“…Song presented a transition‐metal‐free method applied in borylation of terminal alkynes to provide alkylboronates . Fernández's and Morken's group reported the transition‐metal‐free enantioselective diboration of alkenes using chiral reagents.…”
Section: Introductionmentioning
confidence: 99%
“…3 In general, the synthetic reactions involving diboron(4) compounds such as B 2 X 4 , B 2 (NR 2 ) 4 , B 2 (alkyl) n , B 2 (OR) 4 , etc. mainly include borylation reactions, [4][5][6][7][8][9][10][11] diboration reactions, [12][13][14][15][16][17][18] borylative cyclization reactions, [19][20][21] borylative ring opening reactions, [22][23][24][25][26][27] boracarboxylation reactions, 28 hydroboration and carboboration reactions, 29-32 etc. For instance, Miyaura et al 33,34 developed the borylation reactions using dialkoxyboranes or diboron ( 39 reported the rhodium(I)-catalyzed diboration reaction of Estyryl boronate esters with B 2 cat 2 , in which the 1,1,1-triborylalkane is the dominant product.…”
Section: Introductionmentioning
confidence: 99%
“…Szabó et al 41 studied the borylative ring opening reaction of substituted vinylcyclopropanes and vinyl aziridines with tetrahydroxydiboron catalyzed by palladium. Besides the above exemplied reactions catalyzed by the transitional-metal catalyst, there are also many researches on the reactions involving diboron (4) compounds under the transition-metal-free condition, such as borylation reactions, 10,11 diboration reactions [16][17][18] and borylative ring opening reactions, [25][26][27] etc.…”
Section: Introductionmentioning
confidence: 99%